2004
DOI: 10.1007/s00415-004-0313-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial effects and evaluation of the health-related quality of life in patients suffering from well-controlled epilepsy

Abstract: Despite the fact that we studied a relatively small sample of patients with mild epilepsy, our results showed that their HRQOL was obviously affected, while their psychological health remained nearly unaffected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 6 publications
0
12
0
2
Order By: Relevance
“…2,12 PSE impairs self-reported vitality and physical and social functioning. 13 We used a population-based register in a multiethnic area of London, including hospital and community diagnoses of first stroke, to investigate the epidemiology and associations of PSE over 12 years, focusing on long-term rates and predictors of epilepsy.…”
mentioning
confidence: 99%
“…2,12 PSE impairs self-reported vitality and physical and social functioning. 13 We used a population-based register in a multiethnic area of London, including hospital and community diagnoses of first stroke, to investigate the epidemiology and associations of PSE over 12 years, focusing on long-term rates and predictors of epilepsy.…”
mentioning
confidence: 99%
“…Most studies of QoL in seizure-free patients, suggest normal or nearnormal functioning in many aspects of life [25,27,28,58]. Some more recent studies though, have found an impaired QoL (decline in overall QoL, in social and physical function, in symptoms of depression, health concerns and low self-esteem) even in seizure-free patients, and notably, to a higher degree that would 'normally' be expected [2,3,25,26,39]. These unexpected findings show that QoL in patients with epilepsy is determined by more than seizure control and alterations of consciousness [53].…”
Section: Discussionmentioning
confidence: 99%
“…Klinik nöbet özelliklerinin, antiepileptik ilaçlar hastalık süresi, sosyoekonomik durum, eğitim düzeyi yaşam kalitesi üzerine etkileri olduğu gösterilmiştir. [2,10,14] Hastalarımıza diğer toplumlara göre daha iyi aile desteği sağlanması, sosyoekonomik durumlarının daha az etkilenmesi ile ilişkili olabilir. Toplumumuz gibi eğitim düzeyinin düşük olduğu ülkelerde epilepsi hastalarında eğitim düzeyi ile YK arasında bir ilişki de saptanamamasına neden olabilir.…”
Section: Discussionunclassified
“…Özelikle nöbet sıklığının SF36'nın ağrı, fiziksel fonksiyon, mental sağlık alt ölçeklerini belirgin etkilendiği belirtilmektedir. [14] Ancak çalışmamızda SF-36'nın hiçbir alt ölçe-ği ile nöbet sıklığı arasında bir ilişki saptanmamıştır.…”
Section: Discussionunclassified